Exploring cloud architecture. IN Forecast Cloudy. - Fultz, Joseph
Joseph Fultz uses Windows Azure as the context in which to explore general architectural considerations and some base high-level designs for creating cloud-based solutions.
Keywords: Windows Azure; Cloud computing; Platform-as-a-Service (PaaS).; Infrastructure as a Service (IaaS).